Vitis vinifera L. cv. Falanghina Seed Extracts: Antioxidant Effect of Bioactive Compounds on HepG2 Cells - Stefania Iervolino; Pierpaolo Scarano; Jessica Raffaella Madera; Cristina Franco; Maria Tartaglia; Romania Stilo; Rosaria Sciarrillo; Lorella Maria Teresa Canzoniero; Maria Moreno; Carmine Guarino (MDPI AG, 2024)
Vitis vinifera L. is a natural source of bioactive compounds that is already used for cosmeceutical and nutraceutical approaches. However, their phytochemical and antioxidant properties, although studied, have not been fully explored. We aimed to characterize V. vinifera L. cv. Falanghina seed extracts in different polarity solvents (hexane, ethyl acetate, ethanol, and a mixture of acetone-water) for their phytochemical contents, including the total phenolic compound content (TPC), free radical scavenging capacities, and antioxidant ability on HepG2 cells. We directly profiled the functional quality of V. vinifera seed extracts against H2O2-induced oxidative stress in HepG2 cells, focusing on mitochondrial functions. The content of bioactive compounds was characterized by LC-MS. To assess the cytocompatibility of the extracts, a 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay was conducted. Results showed that extraction with ethyl acetate (18.12 mg GAE·g−1) and ethanol solvents (18.07 mg GAE·g−1), through Soxhlet, and with an acetone-water mixture (14.17 mg GAE·g−1), through maceration, yielded extracts rich in (poly)phenols, with good scavenging and antioxidant activity (98.32 I% for ethanol solvents and 96.31 I% for acetone-water mixture). The antioxidant effect of polyphenols is at least partially due to their capacity to maintain mitochondrial biogenesis and mitophagy, which elevates mitochondrial efficiency, resulting in diminished ROS production, hence re-establishing the mitochondrial quality control. These findings highlight the valorization of Vitis by-products to improve food functional characteristics.